Acidic Three‐Liquid‐Phase Microemulsion Systems Based on Balanced Catalytic Surfactant for Epoxidation and Sulfide Oxidation under Mild Conditions. Issue 2 (11th January 2013) - Fressancourt‐Collinet, Marion; Hong, Bing; Leclercq, Loïc; Alsters, Paul. L.; Aubry, Jean‐Marie; Nardello‐Rataj, Véronique
Abstract Didecyldimethylammonium tungstate has been designed as a balanced catalytic surfactant to form acidic three‐liquid‐phase microemulsion systems at room temperature in the presence of water, a non‐chlorinated solvent and dimethyldioctylammonium salts (hydrogen sulfate and dihydrogen phosphate). The triphasic system is efficient for the oxidation of olefins, sulfides and thiophenes under mild conditions. Moreover, the recovery and reusability of the catalyst, the straightforward separation of products and catalysts in two distinct phases as well as the possible use of environmentally friendly solvents such as tert‐butyl acetate, make this system particularly attractive for catalytic oxidation reactions involving hydrogen peroxide as the primary oxidant under acidic or neutral conditions.